Cardiomyopathies : report of a WHO expert committee, meeting held in Geneva from 18 to 23 April 1983 - WHO Expert Committee on Cardiomyopathies; World Health Organization (Geneva : World Health Organization, 1984)
Reviews world knowledge on heart muscle diseases classified as dilated cardiomyopathy, hypertrophic cardiomyopathy, and restrictive cardiomyopathy. A section devoted to pathology outlines the distinguishing morphological and histological features for each group of the cardiomyopathies. Subsequent sections cover haemodynamics, clinical recognition, non-invasive and invasive investigations, current methods of medical and surgical treatment, and factors affecting prognosis. A discussion of pathogenic mechanisms assesses what is known about the causes of hypertrophic cardiomyopathy, the viral theory of dilated cardiomyopathy including myocarditis, and the role of the eosinophil in restrictive cardiomyopathy. The report concludes with summaries of current knowledge on heart muscle disease due to alcohol consumption, amyloid heart disease, peripartal heart disease, cardiac involvement in Chagas' disease, and Keshan disease in China. More than 100 references to the literature are included.
Introduction -- extent of the problem -- Pathology -- Haemodynamics -- Clinical recognition -- Investigations -- Treatment -- Prognosis -- Special problem concerning pathogenetic mechanisms -- Areas for research -- Prevention -- Certain specific heart muscle diseases -- Conclusions and recommendations -- Acknowledgements -- References -- Annex.
Keywords: Cardiomyopathies